2005
DOI: 10.1111/j.1472-8206.2005.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative trial of tramadol/paracetamol and codeine/paracetamol combination tablets on the vigilance of healthy volunteers

Abstract: Combination of tramadol 37.5 mg/paracetamol 325 mg (a), or codeine 30 mg/paracetamol 500 mg (b) or 300 mg have similar pain efficacy but a difference has been suggested concerning their adverse events on vigilance. In clinical practice, combinations are usually given at the above-mentioned dosage three to four times a day. The aim of this study was to compare a single dose of these two combinations (a) and (b) in 24 healthy young volunteers on visual choice reaction time (CRT, ms). Results show a longer CRT (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Codeine is metabolised to morphine in the body, and pain studies suggest that the analgesic effect from codeine is caused by morphine. Experimental studies have shown impairment in traffic related tests, but concentrations of morphine and codeine in blood have not been measured in these studies [6][7][8][9][10]. Codeine was therefore not included on the list on the assumption that morphine levels will identify cases where codeine, morphine, or heroin have been used.…”
Section: Impairment Limitsmentioning
confidence: 99%
“…Codeine is metabolised to morphine in the body, and pain studies suggest that the analgesic effect from codeine is caused by morphine. Experimental studies have shown impairment in traffic related tests, but concentrations of morphine and codeine in blood have not been measured in these studies [6][7][8][9][10]. Codeine was therefore not included on the list on the assumption that morphine levels will identify cases where codeine, morphine, or heroin have been used.…”
Section: Impairment Limitsmentioning
confidence: 99%
“…However, there are few direct comparative studies of combination products – for instance, codeine/paracetamol versus tramadol/paracetamol 131133…”
Section: Overview On Experience With Fixed-dose Tramadol/paracetamol mentioning
confidence: 99%
“…Adult data from postoperative orthopedic pain suggest similar pain scores for tramadol–paracetamol compared to codeine–paracetamol, although the incidence of constipation and vomiting was higher in those given codeine (68). Other data suggest increased somnolence in adults given codeine over tramadol (69); although this may not necessarily be a bad thing in children.…”
Section: Questions and Conclusionmentioning
confidence: 99%